Aktivitas Antimikrob Minyak Atsiri dan Potensinya sebagai Antiseptik : Antimicrobial Activities of Essential Oils and Their Potential as Antiseptics - Rakhman, Ira Meylan Nafarah; Agung Priyanto, Jepri; Astuti, Rika Indri (Departemen Biologi, Institut Pertanian Bogor, 2024)
Pathogenic bacterial infection is one of the leading causes of mortality worldwide. Essential oil-based antiseptic is needed to prevent pathogenic infection. This study aimed to analyze the antimicrobial activity of essential oils and their antiseptic potential. The essential oils used were clove oil, patchouli oil, citronella oil, ginger oil, and nutmeg oil. These oils had various antibacterial activities with inhibition zones ranging from 0.3-1.2 cm against Escherichia coli [ATCC 8739], Pseudomonas aeruginosa [ATCC 15442], and Staphylococcus aureus [ATCC 6538], as tested by agar diffusion method. Nutmeg oil had the largest inhibition zone against of three targeted bacteria. Supporting this result, cell viability test showed nutmeg oil in concentration of 500 ppm and 1,000 ppm could inhibit the growth S. aureus up to 62% and 100%, respectively. Analysis of standardized antiseptic based on SNI: EN 1040:2005 proved that nutmeg oil can be used as antiseptic candidate because it was able to reduce the S. aureus more than 5log10 after contact for 1 minute. Our data indicate nutmeg oil can potentially to be applied as an antimicrobial agent and an ingredient of antiseptic products.